A repair operator for decomposable problems’ global solutions - Barbosa, Vítor (2017)
Trabalho apresentado em 8th European Starting AI Researcher Symposium STAIRS 2016 : European Starting AI Researcher Symposium, 29 de agosto a 2 de setembro de 2016, The Hague, Holanda